2013
DOI: 10.1155/2013/625906
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomics Study of Essential Hypertension and Its Chinese Medicine Subtypes by Using Gas Chromatography-Mass Spectrometry and Nuclear Magnetic Resonance Spectroscopy

Abstract: A metabonomic study was performed to investigate the metabolic mechanism of essential hypertension and its Chinese medicine subtypes, including “Yin-deficiency and Yang-hyperactivity syndrome” (YDYHS) and “Yin-Yang deficiency syndrome” (YYDS). Plasma samples from 22 healthy volunteers, 31 hypertensive patients with YDYHS, and 29 hypertensive patients with YYDS were analyzed by 1H-NMR spectroscopy and gas chromatography coupled with mass spectrometry (GC-MS). The three groups were distinctly classified by princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
0
14
1
Order By: Relevance
“…However, no single metabolomics platform could provide adequate coverage of the entire human metabolome in biosamples 16 . Previous studies have shown that the multiple metabolomics platforms could largely enhance the level of metabolome coverage 17 , 18 . Meanwhile, our previous study found that the combined application of NMR and GC-MS could yield a superior biomarker panel for bipolar disorder (BD) than applying each platform in isolation 19 .…”
Section: Introductionmentioning
confidence: 99%
“…However, no single metabolomics platform could provide adequate coverage of the entire human metabolome in biosamples 16 . Previous studies have shown that the multiple metabolomics platforms could largely enhance the level of metabolome coverage 17 , 18 . Meanwhile, our previous study found that the combined application of NMR and GC-MS could yield a superior biomarker panel for bipolar disorder (BD) than applying each platform in isolation 19 .…”
Section: Introductionmentioning
confidence: 99%
“…With diverse methodologies, the combination of different metabolomics platforms can identify more synthesis metabolites than a single method 19 21 . In the current study, three metabolomics approaches using nuclear magnetic resonance (NMR), gas chromatography–mass spectrometry (GC–MS), and liquid chromatography–mass spectrometry (LC–MS) were combined to determine metabolomics profile alterations in the livers of a mouse model of MDD.…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of the unique advantages of any particular methodology, no single metabonomic platform can provide adequate coverage of the entire human metabonome in any given biological sample21. Previous studies have demonstrated that the use of multiple metabolomics platforms and technologies allowed us to identify several previously unknown urine metabolites and to substantially enhance the level of metabolome coverage222324. Therefore, the combined application of NMR spectroscopy and GC-MS may identify a more comprehensive metabolite panel than any single metabonomic platform alone.…”
mentioning
confidence: 99%